Incentive Compatibility and the Bargaining Problem - Myerson, Roger B. (Econometrica, 1979)
Collective choice problems are studied from the Bayesian viewpoint. It is shown that the set of expected utility allocations which are feasible with incentive-compatible mechanisms is compact and convex, and includes the equilibrium allocations for all other mechanisms. The generalized Nash solution proposed by Harsanyi and Selten is then applied to this set to define a bargaining solution for Bayesian collective choice problems.